Instantaneous Analysis Attribute for Reservoir Characterization at Basin Nova-Scotia, Canada - Ruliyanti Ruliyanti; Puguh Hiskiawan; Artoto Arkundato (UNEJ e-Proceeding, 2016)
Analysis of data seismic attributes used in the Basin of Nova-Scotia, Canada. This analysis aimed to determine the distribution of reservoir and reservoir characterization. Seismic attribute used the instantaneous attributes which included instantaneous amplitude, instantaneous frequency and instantaneous phase while for reservoir characterization used crossplot between instantaneous attributes with well log data. The attribute ran on specified target zone, the attribute analysis to determine the distribution of the reservoir. Crossplot conducted to determine the characteristics or physical properties of the reservoir in the target zone. Furthermore, lithologic and stratigraphic analysis to determine the geological conditions of the target zone. The study was conducted in inline and crossline of Logan Canyon formations. Research results obtained in the form of small fractures that are not visible and the two major faults with direction Northwest-Southeast and has the attributes of instantaneous output value is low. This fault is also the location of a distribution reservoir contained in the target zone. For the reservoir characteristics such as porosity and acoustic impedance range of values obtained respectively, so it can be said that the target zone is dominated by a sandstone reservoir form.